Risk assessment of metachronous gastric cancer development using OLGA and OLGIM systems after endoscopic submucosal dissection for early gastric cancer: a long-term follow-up study - Na, Yun Suk; Kim, Sang Gyun; Cho, Soo-Jeong (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2023)
Background Metachronous gastric cancer (MGC) may develop in patients undergoing curative endoscopic submucosal dissection for early gastric cancer. As gastritis and intestinal metaplasia are notable precursors to gastric cancer, we assessed MGC risk using the Operative Link on Gastritis Assessment (OLGA) and Operative Link on Gastric Intestinal Metaplasia assessment (OLGIM) systems. Methods This retrospective cohort study classified the OLGA and OLGIM stages for 916 patients who had undergone endoscopic submucosal dissection for early gastric cancer between 2005 and 2015. MGC development was followed up until 2020 and risk factors were evaluated using the Cox proportional hazards regression analysis. Results During a median follow-up of 94 months, MGC developed in 120 subjects. OLGA stages II ~ IV were significantly associated with increased MGC risk (hazard ratio [HR] 1.83, 95% confidence interval [CI] 1.05–3.19; HR 2.31, 95% CI 1.22–4.38; HR 2.36, 95% CI 1.16–4.78) in multivariable analysis, even after adjusting for the well-known positive predictor of Helicobacter pylori eradication. OLGIM stages II ~ IV also showed significant association (HR 2.86, 95% CI 1.29–6.54; HR 2.94, 95% CI 1.34–6.95; HR 3.64, 95% CI 1.60–8.29). 5-year cumulative incidence increased with each stage. Helicobacter pylori -eradicated patients with OLGIM stages 0 ~ II had significantly less MGC than non-eradicated patients (4.5% vs 11.8%, p = 0.022), which was not observed with OLGIM stages III ~ IV. Conclusions High OLGA and OLGIM stages are independent risk factors for metachronous gastric cancer, with the OLGIM staging system being a better predictor. Patients with OLGIM stages 0 ~ II are a subgroup that may benefit more from Helicobacter pylori eradication.